Cryptic host-associated differentiation and diversity: unravelling the evolutionary dynamics of the plant pathogen Lasiodiplodia - Ya-Zhu Ko; Huei-Chuan Shih; Meng-Shin Shiao; Yu-Chung Chiang (IMA Fungus)
Lasiodiplodia, a genus within the Botryosphaeriaceae family, comprises significant plant pathogens with a broad host range and global distribution, posing a substantial threat to agricultural production. Our recent study revealed the complexity of this genus by identifying numerous potential cryptic species within the seemingly generalist L. theobromae. To fully understand this species’ complexity, higher-resolution genetic markers are required. Therefore, this study employed a comprehensive analysis of multiple transferable microsatellite markers to verify Lasiodiplodia species delimitation and examine the fine-scale genetic structure and diversity of Lasiodiplodia species, particularly L. theobromae. The study identified four distinct genetic groups within L. theobromae, each showing high genetic diversity. The phylogenetic relationships of these groups align with the evolutionary history of their host plants. This finding suggests that host-pathogen co-evolution is shaped by shared ancestral variation, limited gene flow, isolation and natural selection. These insights enhance our understanding of managing economically important Lasiodiplodia plant pathogens and highlight the significance of genetic diversity and host preferences in developing effective control measures.